Doodle bites - Dunbar, Polly (Walker London, 2009)
Doodle is feeling bitey. Bitey, Bitey! And what's better to bite than a big bottom - Tumpty's! But poor Tumpty is so upset he stamps on Doodle's tail ... and now both of them are upset ... and before long everyone is upset!